Slag performance regulation and control method for large-proportion collaborative smelting of multi-source lead-based solid waste in flash lead smelting
By controlling the Zn, Al content and the addition amount of CaO and SiO2 flux in flash lead smelting technology, the deterioration of slag properties and thermal balance caused by lead-based solid waste are solved, and the slag performance with low viscosity and low energy consumption is achieved, which improves the Production capacity and solid waste disposal capacity.
Patent Information
- Application Number
- CN202411345832.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
AI Technical Summary
The coordinated treatment of lead-based solid waste from multiple sources in flash lead sludge deteriorates and difficult separation of slag lead, and difficult to achieve thermal balance management of furnace furnaces, limiting the improvement of production capacity.
By controlling the Zn, Al content and the addition amount of CaO and SiO2 flux in the batching section, it is ensured that the ZnO content in the slag is not higher than 25 wt.%, the Al2O3 content is not higher than 6 wt.%, and the CaO/SiO2 mass ratio is within the range of 0.30-0.50 The alkalinity is in the range of 1.80-2.30, the slag viscosity is less than 0.5Pa·s and the temperature is less than 1200℃, achieving stability and thermal equilibrium of the slag.
Effectively improves the viscosity of the slag, reduces the temperature of the slag, improves the service life of the resistant materials and water jackets, reduces production energy consumption, increases the absorption capacity of multi-source lead-based solid waste, and promotes the sustainable development of joint smelting of lead-zinc develop.
Smart Images

Figure CN119220825A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for controlling slag properties in large-scale coordinated smelting of multi-source lead-based solid wastes during flash lead smelting, and belongs to the technical field of non-ferrous metal smelting. Background Art
[0002] In the past three decades, direct lead smelting technology has replaced the traditional blast furnace smelting process. On the one hand, my country's lead smelting industry has introduced advanced foreign processes such as Kifset flash lead smelting, and has also independently developed technologies such as SKS oxygen-enriched bottom blowing lead smelting. Currently, lead smelting technology, equipment, production capacity and output are leading the world. However, with the rapid development of the above-mentioned technologies, the tightening and changes in smelting raw materials have become a common problem that hinders the sustainable development of lead smelting companies. The proportion of low-grade and difficult-to-smelt lead and zinc resources and various lead-based solid wastes in smelting raw materials continues to increase, and the coordinated smelting of lead and zinc minerals and renewable resources has become an industry consensus.
[0003] Metallic lead is mainly produced by pyrometallurgy. In the process of pyrometallurgy, solid / hazardous waste disposal is carried out in coordination. The economic and environmental benefits are very prominent, which is the common requirement and technical development direction of the country, society and industry. The pyrometallurgy lead smelting process can be used to treat various waste resources. The valuable components can be comprehensively recovered through various carriers such as crude lead, matte, yellow slag, secondary zinc oxide, flue gas, etc. At the same time, high-temperature glass slag can effectively seal the toxic and harmful elements in hazardous waste, and systematically promote the low-cost resource disposal of solid / hazardous waste and the sustainable development of the industry. Therefore, in the research and development and practice of modern lead smelting technologies such as flash smelting, SKS bottom blowing smelting, oxygen-enriched top blowing smelting, and oxygen-enriched side blowing smelting, the coordinated smelting of secondary wastes from various sources such as hydrometallurgy zinc leaching slag, iron precipitate slag, lead-silver slag, sulfide residue, oxide residue, etc., and there are mature industrial practices in many countries. The successful practices of the cases are based on the long-term accumulation of the basic principles of lead smelting and production experience data, which are unique and cannot be directly referenced and promoted. The process flow, raw material types, and matching proportions adopted by smelters in different countries are different, resulting in significant differences in production technical indicators such as smelting temperature, furnace atmosphere, and lead slag type.
[0004] Lead and zinc smelting enterprises at home and abroad continue to conduct research and development in the areas of reducing slag, clearing inventory and comprehensive recovery of valuable components. Among the many direct lead smelting processes, the flash lead smelting technology of Kiefset Smelting has the characteristics of strong raw material adaptability, large secondary resource processing volume, high degree of equipment automation, and excellent environmental protection indicators in the production process. It shows good potential in the synergistic treatment of multi-source lead-based solid waste with lead concentrate. In 1997, the flash lead smelting project of the Trail Plant of Canada's Cominco Company was completed and put into production. The raw materials entering the furnace included zinc oxygen pressure leaching slag, lead silver slag and other solid wastes, and the total proportion of secondary materials exceeded 50%. Since then, flash lead smelting technology has also been promoted and applied in my country. At present, among the many companies at home and abroad that use flash lead smelting synergistic smelting technology, the proportion of various types of lead-based solid waste in the total materials entering the furnace continues to increase. At the same time, as a large proportion of solid waste slag from various sources is added to the furnace, the Pb grade in the furnace material continues to decrease. The lower the Pb grade of the furnace material, the less conducive it is to the formation of the metallic lead liquid phase layer. In addition, the solid waste slag material has a high impurity content and is prone to form a refractory spinel phase, resulting in adverse effects such as high slag viscosity and poor fluidity. The above changes pose severe challenges to the slag performance control and furnace heat balance management in the flash lead smelting process, and seriously restrict the improvement of the flash furnace production capacity.
[0005] Faced with such problems, the most direct on-site control strategy is to adjust the raw material ratio (maintain a higher Pb grade and lower Zn and Al content in the charge) and increase the furnace temperature (reduce slag viscosity), but this solution has limited effect and many problems, such as increased energy loss, increased boiler load, and reduced life of refractory water jackets. Therefore, scientifically designing the slag composition of flash lead smelting with large proportions of multi-source lead-based solid waste and forming a systematic and replicable slag viscosity control strategy is the only way to solve this technical problem from the source. Summary of the invention
[0006] The purpose of the present invention is to provide a method for controlling the properties of slag in flash lead smelting for large-scale coordinated smelting of lead-based solid wastes from multiple sources, focusing on solving technical problems such as deterioration of slag properties and difficulty in slag-lead separation caused by the coordinated treatment of lead-based solid wastes from multiple sources by existing flash lead smelting technologies.
[0007] The technical solution adopted by the present invention is:
[0008] Step 1: During the batching process, complete the control of Zn and Al content in the mixed charge and the control of CaO and SiO 2 Adjustment of flux addition amount;
[0009] Step 2: During the flash smelting process of Kifuset, the ZnO content in the slag is controlled to be no higher than 25wt.%, and the Al 2 O 3 Content not higher than 6wt.%, CaO / SiO 2The mass ratio range is 0.30-0.50, and the basicity range is 1.80-2.30. At this time, the slag viscosity is less than 0.5 Pa·s and the temperature is lower than 1200℃, which meets the requirements of smooth smelting;
[0010] Step 3: normal slag and lead removal.
[0011] Preferably, the multi-source lead-based solid waste in step 1 includes one or more of hydrometallurgical zinc smelting iron precipitate slag, hydrometallurgical zinc-lead-silver slag, electroplating lead mud, fly ash, lead oxide ore, etc.
[0012] Preferably, the multi-source lead-based solid waste in step 1 accounts for 10-60% of the total material entering the furnace.
[0013] Preferably, the collaborative smelting operation temperature in step 1 is 1150-1350° C., and the oxygen-enriched concentration of the process air is 80-100%.
[0014] Preferably, flash lead smelting is used to smelt ZnO, Al 2 O 3 The content is achieved by metering and controlling the proportion of all types of powder entering the furnace in the batching section.
[0015] Preferably, flash lead smelting is carried out in conjunction with the CaO / SiO 2 The mass ratio is achieved by metering and controlling the addition ratio of lime and quartz flux in the batching section.
[0016] Preferably, the slag system for flash lead smelting and synergistic smelting in step 2 is FeO x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Slag system, the initial slag components include FeO, Fe 2 O 3 , CaO, SiO 2 、ZnO、PbO、Al 2 O 3 The measurement units of the above components are all mass percentages, and the total is 100wt.%.
[0017] Preferably, the viscosity and temperature smelting requirements of the slag in step 2 are: the slag temperature is lower than 1200° C. and the viscosity is less than 0.5 Pa·s.
[0018] Preferably, the ZnO content in the slag of step 2 is calculated based on the +2 valent single oxide form of the Zn element in the slag.
[0019] Preferably, the Al in the slag in step 2 2 O 3 The content is calculated based on the +3 valent single oxide form of Al element in the slag.
[0020] Preferably, the CaO / SiO in the slag of step 2 is 2 The mass ratio is calculated based on the +2-valent single oxide form of the Ca element and the +4-valent oxide form of the Si element in the slag.
[0021] Preferably, the slag basicity calculation formula in step 2 is: In formula 1, m(Me x O y ) refers to the mass fraction of various oxide components in the slag.
[0022] Preferably, the ZnO content and Al content in the slag in step 2 are 2 O 3 Content, CaO / SiO 2 The control range of mass ratio and alkalinity is determined based on two important parameters: the temperature corresponding to the slag viscosity of 0.5 Pa·s and the temperature of the mutation point of the viscosity test curve. The temperature corresponding to the slag viscosity of 0.5 Pa·s is equivalent to the slag temperature in actual industrial practice, which directly affects the production energy consumption. The temperature of the mutation point of the viscosity test curve is the limiting temperature at which the slag viscosity increases rapidly. If the slag temperature is lower than this point, it is very easy to cause the slag to solidify and the slag lead to be difficult to separate.
[0023] Preferably, the hydrometallurgical zinc smelting iron precipitated slag is one or more of goethite slag, hematite slag and jarovanadium slag produced by the zinc smelting iron removal system.
[0024] Preferably, the hydrometallurgical zinc-lead-silver slag is silver-containing lead sulfate waste slag produced by a zinc smelting hot acid leaching system or a high-temperature high-acid leaching system.
[0025] Preferably, the electroplating sludge is lead-containing slag sludge produced by the production process and water treatment process of the electroplating industry.
[0026] Preferably, the fly ash is lead-containing fly ash captured by a lead smelting dust collection system.
[0027] Preferably, the lead oxide ore is a refractory low-grade lead ore produced by a mining and dressing system, and lead is mainly present in the ore in an oxidized state.
[0028] The method of the present invention is based on the following basic theory:
[0029] FeO x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 The slag belongs to silicate type slag, the basic structural unit of which is silicate tetrahedron [SiO 4 ] 4- , forming a silicate network structure. The oxygen present in this type of slag is divided into three types: chain-linked oxygen O0 , non-chain-linked oxygen O - and free oxygen O 2- , and is in a state of chemical equilibrium:
[0030]
[0031] Each silicate tetrahedron has O - The number of NBO / T is used to represent the degree of polymerization of the silicate slag melt structure. The lower the value, the higher the degree of polymerization of the slag. Since viscosity involves the transmission between adjacent liquid layers, the longer the chain length (or the higher the degree of polymerization), the more difficult the transmission is, so the greater the melt viscosity. As basic oxides such as ZnO and CaO are added to the slag, Si 4+ O 2- Combined, more O is generated in the silicate structure - , the degree of slag aggregation decreases and the viscosity decreases. Chemical reactions that occur include:
[0032]
[0033] With the amphoteric oxide Al 2 O 3 and acidic oxide SiO 2 Added into alkaline slag, it will react with [SiO 4 ] 4- Combination, O in the silicate structure - The slag aggregation degree and viscosity increase.
[0034] In addition, the above oxide components in FeO x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Adding it to the slag system will also increase the crystallization ability of the slag, generate a high melting point solid phase, and cause chemical reactions such as:
[0035] ZnO+Al 2 O 3 =ZnAl 2 O 4 (Formula 4)
[0036] ZnO+Fe 2 O 3 =ZnFe 2 O 4 (Formula 5)
[0037] FeO+Al 2 O 3 =FeAl 2 O 4 (Formula 6)
[0038] The melting point of the spinel phase is extremely high, exceeding 1800°C, and it precipitates in the liquid slag, causing the viscosity to increase. x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 The viscosity of the basic slag, ZnO and Al in the slag 2 O 3 , CaO, SiO 2 The component content needs to be reasonably limited in order to obtain low viscosity values suitable for plant operation at lower temperatures.
[0039] The method of the present invention is based on the following experimental studies:
[0040] According to the process characteristics of large-scale synergistic smelting of multi-source lead-based solid wastes by flash lead smelting technology, the addition ratios of multi-source lead-based solid wastes and process air oxygen concentrations were set in various synergistic smelting processes, and 15 groups of industrial slags with different target compositions were obtained for viscosity testing.
[0041] Table 1 shows the relevant information of 15 groups of co-smelting slags with different target compositions, including ZnO content, Al 2 O 3 Content, CaO / SiO 2 Except for mass ratio and slag basicity, other slag composition data are not listed.
[0042] Table 1 Relevant information of different synergistic smelting slags
[0043]
[0044] For the 13 groups of slags in Table 1, a TDN-531 high temperature viscometer was used to perform a cooling continuous viscosity test at 1350°C using the inner cylinder rotation method. The crucible (inner diameter 33mm, outer diameter 35mm, height 100mm) and rotor used in the test process were made of high-purity molybdenum, and the atmosphere was high-purity nitrogen (oxygen potential V O2 / V N2 =10 -7 ).
[0045] Before the viscosity test, the high temperature viscometer parameters were calibrated using 717a standard glass, and the subsequent operating procedures were carried out according to the regulations.
[0046] During the test, computer software was used to accurately control the temperature of the equipment and record data, with a temperature control accuracy of ±1°C.
[0047] According to the results of 13 sets of temperature-viscosity test curves, the ZnO content, Al 2 O 3Content, CaO / SiO 2 The influence of mass ratio and slag basicity on slag viscosity is studied to obtain the reasonable control range of the above four factors.
[0048] The invention has the beneficial effects that: according to the slag composition characteristics produced by the process of flash lead smelting with large proportion of synergistic smelting of multi-source lead-based solid waste, the invention proposes a FeO x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 ZnO content and Al content in the system slag 2 O 3 Content, CaO / SiO 2 The method for regulating mass ratio and alkalinity mainly solves the production technical problems such as deterioration of slag properties and large fluctuations in furnace heat balance caused by the large proportion of multi-source lead-based solid wastes such as hydrometallurgical zinc precipitation slag, hydrometallurgical zinc-lead-silver slag, fuming furnace water quenching slag, smelting soot, lead oxide ore, etc. in the flash lead smelting raw materials. The present invention strictly controls the content of elements such as Zn and Al in the materials entering the furnace and the amount of lime and quartz flux added in the batching stage, so as to maintain the slag composition at a reasonable ZnO content, Al content and other levels at the source of smelting. 2 O 3 Content, CaO / SiO 2 Within the mass ratio and alkalinity range, it can stably process a higher proportion and more types of lead-based solid waste, while effectively improving the slag viscosity to below 0.5pa·s and reducing the slag temperature to below 1200°C. The above regulation can increase the service life of refractory materials and water jackets, reduce production energy consumption costs, increase the capacity to absorb multi-source lead-based solid waste, and promote the sustainable development of lead-zinc joint smelting. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 It is FeO of Example 1 of the present invention x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Curve of slag viscosity changing with temperature
[0050] Figure 2 It is FeO of Example 2 of the present invention x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Curve of slag viscosity changing with temperature
[0051] Figure 3 It is FeO of Example 3 of the present invention x -CaO-SiO 2 -ZnO-PbO-Al2 O 3 Curve of slag viscosity changing with temperature
[0052] Figure 4 It is FeO of Example 4 of the present invention x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Curve of slag viscosity changing with temperature
[0053] Figure 5 It is FeO of Example 5 of the present invention x -CaO-SiO 2 -ZnO-PbO-Al 2 O 3 Curve of slag viscosity changing with temperature DETAILED DESCRIPTION
[0054] The present invention is further described in detail below with reference to the accompanying drawings and specific implementation examples.
[0055] Production data were obtained in a flash lead smelting furnace using the original comparative example 1, comparative example 2 and the method of the present invention. The main chemical composition, viscosity properties of the slag and the production status of the furnace are shown in Table 2.
[0056] Table 2 Main chemical composition, viscosity properties and furnace production of the slag of the present invention
[0057]
[0058] See also Figure 1 Table 2, Al in the flash lead slag of Example 1 2 O 3 The content is reduced to 4wt.%, and the basicity is in the range of 1.8-2.3. At this time, the slag viscosity is 0.5Pa·s and 0.8Pa·s, and the corresponding temperature is lower than 1200°C. Compared with Comparative Example 1, its slag properties are significantly better, and the material processing capacity of the flash furnace is improved and the energy consumption is reduced.
[0059] See also Figure 2 As shown in Table 2, the ZnO content in the flash lead slag of Example 2 increased to 25wt.%, Al 2 O 3 The content is reduced to less than 6wt.%, and the basicity is in the range of 1.8-2.3. At this time, the slag viscosity is 0.5Pa·s and 0.8Pa·s, and the corresponding temperature is still below 1200°C. Compared with Comparative Example 1, the slag properties are significantly better, and the material processing capacity of the flash furnace is improved. However, the ZnO content in the slag has reached the upper limit of the method of the present invention, and more reducing agents need to be used in the electric furnace reduction stage of the flash furnace, so the energy consumption increases.
[0060] See also Figure 3 and Table 2, Al in the flash lead slag of Example 3 2 O 3 The content is reduced to 6wt.%, and the basicity is in the range of 1.8-2.3. At this time, the slag viscosity is 0.5Pa·s and 0.8Pa·s, and the corresponding temperature is lower than 1200°C. Compared with Comparative Example 2, its slag properties are significantly better, and the material processing capacity of the flash furnace is improved and the energy consumption is reduced.
[0061] See also Figure 4 , Figure 5 Table 2, Al in the flash lead slag of Example 4 and Example 5 2 O 3 The content is reduced to 4wt.%, CaO / SiO 2 The mass ratio is in the range of 0.3-0.5, and the basicity is in the range of 1.8-2.3. At this time, the slag viscosity is 0.5Pa·s and 0.8Pa·s, and the corresponding temperature is lower than 1200°C. Compared with Comparative Example 2, its slag properties are significantly better, and the material processing capacity of the flash furnace is improved and the energy consumption is reduced.
Claims
1. A method for controlling slag properties in flash lead smelting with large proportion of synergistic smelting of multi-source lead-based solid waste, characterized in that: The following steps are involved: Step 1, control the proportion of multi-source lead-based solid waste in the materials entering the furnace, the content of elements such as Zn and Al in the materials entering the furnace, and the amount of CaO and SiO2 flux added, and start coordinated smelting; Step 2: During the flash smelting process, the ZnO content in the slag is controlled to be less than 25wt.%, the Al2O3 content is less than 6wt.%, the CaO / SiO2 mass ratio is in the range of 0.30-0.50, the basicity is in the range of 1.80-2.30, and the slag viscosity and temperature meet the smelting requirements; Step 3, remove slag and lead.
2. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The multi-source lead-based solid waste in step 1 includes one or more of the materials such as hydrometallurgical iron precipitate slag, hydrometallurgical zinc-lead-silver slag, electroplating lead mud, fly ash, lead oxide ore, etc.
3. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The multi-source lead-based solid waste in step 1 accounts for 10%-60% of the total materials entering the furnace.
4. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The coordinated smelting temperature in step 1 is 1150-1350° C., and the oxygen-enriched concentration of the process air is 80%-100%.
5. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The slag system of step 2 is FeO x -CaO-SiO2-ZnO-PbO-Al2O3 slag system.
6. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The requirements for slag viscosity control and temperature smelting in step 2 are: slag temperature is lower than 1200° C. and viscosity is lower than 0.5 Pa·s.
7. The method for controlling slag properties of large-scale synergistic smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The ZnO content in the slag of step 2 is calculated based on the +2 valent single oxide form of the Zn element in the slag.
8. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The Al2O3 content in the slag of step 2 is calculated based on the +3 valent single oxide form of the Al element in the slag.
9. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 1, characterized in that: The CaO / SiO2 mass ratio in the slag of step 2 is calculated based on the +2-valent single oxide form of the Ca element and the +4-valent oxide form of the Si element in the slag.
10. The method for controlling slag properties of flash lead smelting with large proportion of synergistic smelting of multi-source lead-based solid waste according to claim 1, characterized in that: The slag basicity of step 2 is calculated according to the formula Calculation, in formula 1, m(Me x O y ) refers to the oxide Me in the slag x O y The mass fraction of , wherein Me is one of Fe, Ca, Zn, Pb, Si, and Al, and x=1 or 2, y=1 or 2 or 3.
11. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes in flash lead smelting according to claim 2, characterized in that: The hydrometallurgical zinc smelting iron precipitation slag is one or more of goethite slag, hematite slag and jarosite vanadium slag produced by the zinc smelting iron removal system.
12. The method for controlling slag properties of flash lead smelting with large proportion of synergistic smelting of multi-source lead-based solid waste according to claim 2, characterized in that: The hydrometallurgical zinc-lead-silver slag is silver-containing lead sulfate waste slag produced by a zinc smelting hot acid leaching system or a high-temperature high-acid leaching system.
13. The method for controlling slag properties of flash lead smelting and large-scale synergistic smelting of multi-source lead-based solid waste according to claim 2, characterized in that: The electroplating sludge is lead-containing slag mud produced by the production process and water treatment process of the electroplating industry.
14. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes by flash lead smelting according to claim 2, characterized in that: The soot is lead-containing soot captured by a lead smelting dust collection system.
15. The method for controlling slag properties of large-scale coordinated smelting of multi-source lead-based solid wastes in flash lead smelting according to claim 2, characterized in that: The lead oxide ore is a low-grade lead ore that is difficult to smelt and produced by a mining and dressing system. Lead is mainly present in the mineral in an oxidized state.
Citation Information
Cited By
Lead slime separation and recovery method for lead-acid storage battery
CN120425164A
A method for separating and recovering lead sludge for lead-acid storage batteries
CN120425164B
Method for directionally regulating and controlling slag in step-by-step slagging in tin-rich secondary material reduction smelting
CN122428127A
